Disputes in aesthetic practice: what can be done?. (2nd April 2021) - Martin, Ross
Abstract : Disputes, grievances and complaints are increasing, but aesthetic practitioners often do not have the experience to handle these matters, and they are usually instructed to pass these over to their insurers. Dr Ross Martin explains the role of mediator and how they can help in such disputes